Implementation of visual motor ability enhancement program for 5 years old - DİBEK, ESİN (ELSEVIER SCIENCE BV, 2012)
The aim of this study was to test the effectiveness of Visual Motor Ability Enhancement Program (VMAEP) designed to improve visual perception, motor coordination and visual-motor integration skills in 5-year-old children. Participants were a total of 33 five-year-old children, 17 in the experimental group and 16 in the control group. Data collection instruments were family child information form and Visual Perception (VP), Motor Coordination (MC) and Visual-Motor Integration (VMI) Tests (Beery, 2004) in order to test the program. The resulting pretest posttest mean scores showed a statistically meaningful difference in favor of the posttest in the VP, MC and VMI dimensions in the experimental group, and in the VP dimension in the control group. In the posttest comparisons of the experimental and control groups, a statistically meaningful difference in favor of the former was found in the VP, MC and VMI dimensions. In sum, the VMAEP support VP, MC and VMI skills.
Keywords: Preschool; visual motor integration; OCCUPATIONAL-THERAPY SERVICES; FINE MOTOR; FUNCTIONAL PERFORMANCE; SKILLS; INTERVENTION; INTEGRATION; CHILDREN